ARTIFICIAL INTELLIGENCE-THE HIGH STAGE OF THE DEVELOPMENT OF SCIENCE AND TECHNOLOGY (SOCIO-PHILOSOPHICAL ANALYSIS) (Scientific journal of the Fergana State University, 2023)
The article analyzes the philosophical problems of artificial intelligence, which has become one of the most important spheres of public life, the role of artificial intelligence, information and information technologies in the development of society, presents the development of information analysis as a mechanism for social progress, the solution of existing problems and promising tasks in this area.